Genus-Specific Carbon Fixation Activity Measurements Reveal Distinct Responses to Oxygen among Hydrothermal Vent Campylobacteria - McNichol, Jesse; Dyksma, Stefan; Mußmann, Marc; Seewald, Jeffrey S; Sylva, Sean P; Sievert, Stefan M (Applied and environmental microbiology, 2022)
Molecular surveys of low temperature deep-sea hydrothermal vent fluids have shown that (previously ) often dominate the microbial community and that three genera, , , and , frequently coexist. In this study, we used replicated radiocarbon incubations of deep-sea hydrothermal fluids to investigate activity of each genus under three experimental conditions. To quantify genus-specific radiocarbon incorporation, we used newly designed oligonucleotide probes for , , and to quantify their activity using catalyzed-reporter deposition fluorescence hybridization (CARD-FISH) combined with fluorescence-activated cell sorting. All three genera actively fixed CO in short-term (∼ 20 h) incubations, but responded differently to the additions of nitrate and oxygen. Oxygen additions had the largest effect on community composition, and caused a pronounced shift in community composition at the amplicon sequence variant (ASV) level after only 20 h of incubation. The effect of oxygen on carbon fixation rates appeared to depend on the initial starting community. The presented results support the hypothesis that these chemoautotrophic genera possess functionally redundant core metabolic capabilities, but also reveal finer-scale differences in growth likely reflecting adaptation of physiologically-distinct phylotypes to varying oxygen concentrations . Overall, our study provides new insights into how oxygen controls community composition and total chemoautotrophic activity, and underscores how quickly deep-sea vent microbial communities respond to disturbances. Sulfidic environments worldwide are often dominated by sulfur-oxidizing, carbon-fixing . Environmental factors associated with this group's dominance are now understood, but far less is known about the ecology and physiology of members of subgroups of chemoautotrophic . In this study, we used a novel method to differentiate the genus-specific chemoautotrophic activity of three subtypes of In combination with evidence from microscopic counts, chemical consumption/production during incubations, and DNA-based measurements, our data show that oxygen concentration affects both community composition and chemoautotrophic function . These results help us better understand factors controlling microbial diversity at deep-sea hydrothermal vents, and provide first-order insights into the ecophysiological differences between these distinct microbial taxa.